Comparative isotopic natural history of two native passerines (Troglodytes cobbi and Cinclodes antarcticus) and the invasive rats (Rattus norvegicus) that extirpate them. (20th April 2016) - Tabak, Michael A.; Anderson, Orea R. J.; Robb, Gillian; Poncet, Sally; Passfield, Ken; Martinez, Melissa Gaste; Martinez Del Rio, Carlos
Abstract: While several studies have shown that invasive rats can have negative effects on island birds through predation (both direct predation and nest predation), other mechanisms for the effects of invasives on island biota have been given less attention. Here, we explore another potential mechanism by which invasive rats can affect native island birds: the competitive use of common resources. We used stable isotope analyses to estimate the fraction of marine and terrestrial sources incorporated into the tissues of two species of passerines ( Troglodytes cobbi, Troglodytidae; and Cinclodes antarcticus, Furnariidae) and Norway rats ( Rattus norvegicus, Muridae) in the Falkland Islands. These two passerines are absent on islands where rats are present. We found significant incorporation of marine resources in the three species, with the highest incorporation in tissues of T. cobbi . This species appears to be one of the passerines most reliant on marine sources and the most marine member of the family Troglodytidae. We also used the results of these isotopic analyses to estimate the isotopic niche breadth of each of these species and the isotopic niche overlap among them. Rattus norvegicus had a large isotopic niche that overlapped broadly with those of the two passerine species. We propose that different ways of both depicting and estimating isotopic niche widths are complementary rather than alternative. Our results are consistent with the notion that invasive rats might have an impact on these two species of Falkland Island passerines by using common resources but do not rule out the possibility that part of their effect is through direct predation.